Allopathic, AYUSH and informal medical practitioners in rural India – a prescription for change - Shailaja Chandra (Journal of Ayurveda and Integrative Medicine, 2018)
This paper looks at the treatment seeking behaviour of rural households and presents factors that discourage them from using public health facilities. It also brings out how Allopathic medical graduates as well as institutionally qualified AYUSH doctors predominantly offer services in cities and townships which results in lakhs of village households having to depend on unqualified medical practitioners as the first line of medical treatment; also how this situation will continue unless the approach to providing medical treatment is modified. Continued dependence on unqualified practitioners is fraught with dangers of incorrect diagnosis, irrational drug use, resulting in the spread of multi-drug resistance. The reality that surrounds Allopathic practice by AYUSH doctors has also been described along with the educational underpinnings of accepting this approach.We opine that existing state policies that legitimise Allopathic practice by non-Allopathic practitioners do not help the rural poor to access proper medical treatment for acute conditions. Also, it does not enhance the credibility of the indigenous systems of medicine among which Ayurveda is the dominant system. First, we position our views in the context of the recently introduced National Medical Commission (NMC) Bill 2017 and provisions which call for the assessment of the need for human resources for health and building a road map to achieve the same. Second, we advocate re-inventing the pre-independence system of trained medical auxiliaries enrolled on a new schedule of the respective state medical register, authorised to give immediate medical treatment and making informed referrals for further diagnosis or specialised treatment. Finally, we recommend reinforcing the AYUSH systems to tackle emerging non-communicable diseases which are affecting all population cohorts adversely and, in whose prevention and management, the AYUSH systems are reported to possess special skills and competence. Keywords: Health workforce, Rural India, Unqualified practitioners